Soul a comparative approach - Kanzian, Christian, 1963-; Legenhausen, M. (Frankfurt : Ontos Verlag, 2010)
"The leading idea of the book is to focus on the common roots of Islamic and Western traditions and to increase awareness of the chances of systematic philosophical dispute, with the aim to promote a substantial dialogue on an academic level." --back cover.
International conference proceedings.
Includes bibliographical references.
Description based on print version record.
Keywords: Soul -- Islam -- Congresses; Soul -- Christianity -- Congresses; Islamic philosophy -- Congresses; Theology, Doctrinal -- Congresses; RELIGION / Islam / Theology; Electronic books